PUBLIC-PRIVATE PARTNERSHIP MODEL IN REGIONAL INFRASTRUCTURE DEVELOPMENT - Muhammad Ridho Alcaesar; Gunawan Widjaja (CV. Adiba Aisha Amira, 2025)
Regional infrastructure development is a key factor in driving economic growth and improving people's quality of life. However, limited local government budgets are often the main obstacle in providing adequate infrastructure. The public-private partnership (PPP) model comes as an innovative solution by involving private sector participation in infrastructure financing, development and management. This study aims to analyse the concept, implementation, best practices, and challenges of PPP model in the context of regional infrastructure development through literature review. The results show that PPP is able to improve efficiency, service quality, and accelerate the realisation of infrastructure projects, especially through proportional risk and responsibility sharing between the government and the private sector. However, the successful implementation of PPP is highly influenced by a clear regulatory framework, transparent governance, institutional capacity of local government, and community participation. Thus, regulatory strengthening, capacity building, and multi-stakeholder engagement are key in optimising the public-private partnership model for sustainable regional infrastructure development